2009
DOI: 10.3928/1081597x-20090917-06
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of INTRACOR Femtosecond Laser Treatment for Presbyopia

Abstract: The INTRACOR procedure for presbyopia showed good visual acuity outcomes in the early postoperative period. The short treatment time in combination with maintained corneal integrity suggests this new technique has good potential for the treatment of presbyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 29 publications
2
44
0
3
Order By: Relevance
“…Holzer et al recently reported the longest follow-up results from use of this technique [35,36]. After 18 months, median UCNVA had improved significantly from 0.7 log -MAR preoperatively to 0.2 log MAR (P \ 0.001) and the median corneal true net power increased significantly by 1.1-0.9 D (P \ 0.001).…”
Section: Intrastromal Femtosecond Ring Incisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holzer et al recently reported the longest follow-up results from use of this technique [35,36]. After 18 months, median UCNVA had improved significantly from 0.7 log -MAR preoperatively to 0.2 log MAR (P \ 0.001) and the median corneal true net power increased significantly by 1.1-0.9 D (P \ 0.001).…”
Section: Intrastromal Femtosecond Ring Incisionsmentioning
confidence: 99%
“…Five concentric rings are cut within the area 2.0 and 4.0 mm from the line of sight. This should be marked before surgery by using the first Purkinje image [35].…”
Section: Intrastromal Femtosecond Ring Incisionsmentioning
confidence: 99%
“…This laser, most commonly used to create LASIK flaps, can be used to cut corneal and intraocular tissues precisely. Proposed corneal procedures include the creation of intrastromal annular incisions to treat presbyopia, 65 laser-assisted astigmatic keratotomy incisions for the treatment of astigmatism, 66 penetrating cornea incisions for use in refractive lens surgery, 67 and the creation of intrastromal pockets for the placement of corneal inlays. 68 Lens-based femtosecond procedures include the creation of an anterior or posterior capsulotomy and disassembling the lens nucleus for easy removal by aspiration.…”
Section: Refractive Surgery Technologies On the Horizonmentioning
confidence: 99%
“…Recent studies showed that three-layer intrastromal photodisruption by the fs laser in the midperiphery of the stroma can flatten the cornea, possibly because of tissue relaxation [15]. Another study has shown that isolated intrastromal keratotomy using the fs laser technique will be clinically useful for correction of presbyopia (INTRACOR™) [18]. Nevertheless, the mechanisms for remodeling corneal curvature and thickness by intrastromal tissue modeling remain poorly understood.…”
Section: Clinical Perspectivesmentioning
confidence: 99%